Mécanismes neuronaux pour la communication chez les primates - Julia Sliwa; Daniel Y Takahashi; Stephen V Shepherd (Revue de Primatologie)
Primates, like all animals live in an environment that includes others. They can be detected by others and can influence the likelihood (and consequences) of this detection by sending signals. Signals are bodily features or behaviors of the signaler that trigger specific behaviors in the receiver. The receiver, signaler, signal and medium are the four basic building blocks of any communication cycle. Each component can be considered separately, but in the service of communication they are interdependent and defined only in relation to one other. Cycles of reciprocal signal exchange mediate social interactions, but even “asocial” species coordinate reproduction, manage conflict over territory, and may anticipate and influence potential predators and prey. Communication arose long before the evolution of primates, animals and even neurons, yet is a crucial aspect of primate behavior and of their nervous system evolution. In this review, we examine how exchanges take place among primates and how neural systems act to mediate them.